(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Salt and drought stresses are being quite similar considered as two major constraints in maize production. To explore the anatomical bases of resistance to salt and drought stresses, 14 days old seedlings of three maize hybrid genotypes were subjected to salt (100 mM NaCl) and drought stress (equiosmotic PEG-6000) under hydroponic conditions. The experiment was laid out following a completely randomized design having four replicates. Root protoxylem and metaxylem thickness and root diameter were found to be unaffected in both of the drought resistant genotypes in response to salt and drought stresses whereas root protoxylem thickness increased (33.8 and 112.8% by salt and drought stress, respectively) in sensitive genotype (BARI hybrid maize-7). Bundle sheath thickness was found to increase in response to stresses (58.4 and 59.3% by salt and drought stress, respectively) in BARI hybrid maize-12. BARI hybrid maize-12 showed unaffected response in leaf epidermal thickness, phloem area, xylem area and total leaf thickness under both salt and drought stresses J. Bangladesh Agril. Univ. 16(1): 47-55, April 2018